Respuesta :
Answer:
The answer is option 1.
Step-by-step explanation:
You have to use Distributive Laws,
[tex]a(b + c) = ab + ac[/tex]
So for this question :
[tex](6r - 1)( - 8r - 3)[/tex]
[tex] = 6r( - 8r) + 6r( - 3) - 1( - 8r) - 1( - 3)[/tex]
[tex] = - 48 {r}^{2} - 18r + 8r + 3[/tex]
[tex] = - 48 {r}^{2} - 10r + 3[/tex]
The product of the expression is (6r - 1) (-8r - 3) is negative 48 r squared minus 10 r + 3.
What is an algebraic expression?
Algebraic expression is a mathematical equation in which one or both sides is an algebraic expression, such as 2x + 7y = 3.
According to this question, the following expression is given:
(6r - 1) (-8r - 3)
- 6r × -8r = -48r²
- - 1 × -8r = 8r
- 6r × -3 = -18r
- -1 × -3 = 3
Therefore, the product of the expression is -48r² -10r + 3
Learn more about algebra at: https://brainly.com/question/953809
#SPJ9